ФІНАНСОВА ДІЯЛЬНІСТЬ СТРАХОВИКА: КОНЦЕПТУАЛЬНІ ЗАСАДИ ТЕОРІЇ І ПРАКТИКИ - Налукова, Наталія Ігорівна; Бадида, Марія Петрівна (Науковий журнал «Світ фінансів», 2017)
Налукова Н. І., Бадида М. П. Фінансова діяльність страховика: концептуальні засади теорії і практики. Розглянуто основні теоретичні підходи до визначення поняття “фінансова діяльність” та ообґрунтовано авторське трактування терміна “фінансова діяльність страховика”. Проведено аналіз динаміки і структури коштів страхових резервів страховиків України. Аргументовано існуючі тенденції у структурі активів, якими представлені кошти резервів зі страхування життя та кошти технічних резервів. Систематизовано чинники, що мали вплив на структуру активів, якими представлено кошти страхових резервів. Визначено заходи, що сприятимуть покращенню фінансової діяльності страховиків. Налукова Н. И., Бадыда М. П. Финансовая деятельность страховщика: концептуальные основы теории и практики. Рассмотрены основные теоретические подходы к определению понятия “финансовая деятельность” и обоснованно авторское определение термина “финансовая деятельность страховщика”. Проанализирована динамика и структура страховых резервов страховщиков Украины. Определены тенденции в структуре активов, которыми представлены средства резервов по страхованию жизни и средства технических резервов. Систематизированы факторы, повлиявшие на структуру активов, которыми представлены средства страховых резервов. Определены мероприятия, способствующие улучшению финансовой деятельности страховщиков. Nalukova N., Badyda M. The financial activity of insurers: theory and practice.Introduction. Financial activities of insurers requires research aimed at identifying and developing recommendations to promote optimal formation of insurance reserves from various sources and ensure their effective investment in assets allowed.Purpose. To study the theoretical aspects of the insurer’s financial practices nature and to analyze the formation and placement of insurance reserves of insurers in Ukraine.Results. The interpretation of the “financial activity of the insurer” is suggested and the factors that determine its peculiarities are identifies. The results of analysis of the dynamics and structure of insurance reserves in Ukraine such: there was an increase in life insurance reserves; the largest increase in life insurance reserves took place by life insurance contracts, which obligations are defined in convertible currencies; increasing the share of life insurance reserves is the result of the impact of economic, political and military risks and caused by negative expectations about the financial security in both the short and the long term; among the most attractive assets for the allocation of insurance reserves dominated assets with the highest liquidity.Conclusion. In order to improve the financial performance of insurers is necessary: to develop incentives to priority investments of insurance reserves will be securities with fixed income, government bonds, bank gold, real estate, and basic criterion placement of insurance reserves should minimize investment risk and liquidity of assets; to change the existing legislation so as to protect the deposits of insurers which are covered by insurance reserves; to make changes to current legislation on the protection of deposit insurers; to provide tools for forming long-term placement of insurance reserves by using the state guarantees.